Necrosulfonamide Ameliorates Neurological Impairment in Spinal Cord Injury by Improving Antioxidative Capacity - Jiao, Jianhang; Wang, Yang; Ren, Pengfei; Sun, Shicai; Wu, Minfei (Frontiers in Pharmacology, 2020)
Currently, there is no efficient therapy for spinal cord injury (SCI). Anoxemia after SCI is a key problem, which leads to tissue destruction, while hypoxia after SCI induces cell injury along with inflammation. Mixed-lineage kinase domain-like protein (MLKL) is a critical signal molecule of necroptosis, and mitochondrial dysfunction is regarded as one of the most pivotal events after SCI. Based on the important role of MLKL in cell damage and potential role of mitochondrial dysfunction, our study focuses on the regulation of MLKL by Necrosulfonamide (NSA) in mitochondrial dysfunction of oxygen-glucose deprivation (OGD)-induced cell damage and SCI-mice, which specifically blocks the MLKL. Our results showed that NSA protected against a decrease in the MMP, ATP, GSH, and SOD levels and an increase in ROS and MDA levels. NSA also improved the locomotor function in SCI-mice and OGD-induced spinal neuron injury through inhibition of MLKL activation independently of RIP3 phosphorylation. Besides the protective effects, NSA exhibited a therapeutic window. The optimal treatment time was within 12 h after the injury in the SCI-mice model. In conclusion, our data suggest a close association between the NSA level inhibiting p-MLKL independently of RIP3 phosphorylation and induction of neurological impairment by improving antioxidative capacity after SCI. NSA ameliorated neurological impairment in spinal cord injury, which just inhibited MLKL-dependent necroptosis. It also provides a theoretical basis for further research and application of NSA in the treatment of SCI.